2017
DOI: 10.1021/acs.jced.6b00688
|View full text |Cite
|
Sign up to set email alerts
|

Density, Viscosity, and Freezing Point for Four Binary Systems of n-Dodecane or Methylcyclohexane Mixed with 1-Heptanol or Cyclohexylmethanol

Abstract: K and the pressure P = 0.1 MPa for binary mixtures of n-dodecane or methylcyclohexane with 1-heptanol or cyclohexylmethanol have been carried out over the whole composition range. Densities were measured with a vibrating-tube densimeter. Viscosities were determined by an automatic microviscometer based on the rolling-ball principle. The excess molar volumes (V m E ) and viscosity deviations (Δη) were calculated with experimental data and fitted to the Redlich−Kister equation. The results of these excess or dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…All pure compound data obtained in this work are shown in Table . Our results are in agreement with data from the literature for anisole, , dodecane, hexadecane, decalin, , and 1,4-dioxane. , The comparison of experimental densities is shown in Figure a, and it is observed that all absolute relative deviation (ARD(%)) values are below 0.2%, as presented in Figure b. Viscosity measurements are shown in Figure a with all ARD(%) values within 4%, as observed in Figure b.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All pure compound data obtained in this work are shown in Table . Our results are in agreement with data from the literature for anisole, , dodecane, hexadecane, decalin, , and 1,4-dioxane. , The comparison of experimental densities is shown in Figure a, and it is observed that all absolute relative deviation (ARD(%)) values are below 0.2%, as presented in Figure b. Viscosity measurements are shown in Figure a with all ARD(%) values within 4%, as observed in Figure b.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The dotted line (•••) represents the PR-EoS model with parameters reported in Table 3. 22 (blue circle open), Zhao et al 23 (blue triangle up open), Zhang et al 24 (blue boxbar), Prak et al 25 (blue cross), Liu and Zhu 26 (blue diamond open), Sirbu et al 27 (pink triangle left-pointing open), Prak et al 28 (pink plus), Aissa et al 29 (pink triangle down open), Wang et al 30 (pink pentagon open), Esteban et al 31 (pink vertical bar), Omota et al 34 (black hexagon open), Habibullah et al 35 (black symmetry), Qin et al 32 (gray square dotted), Silva et al 33 (gray circle bar). The dotted line (•••) represents the PR-EoS + MHV + NRTL + FT modeling using parameters reported in Tables 3 and 4.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“… a Standard uncertainties u ( T ) = 0.01 K, u ( P ) = 0.2 kPa, u r (ρ) = 0.0005, u r (η) = 0.01. b Reference . c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . k Reference . l Reference . m Reference . n Reference . …”
Section: Methodsmentioning
confidence: 99%
“…For the two binary mixtures of cyclopropane­methanol +1,2,3,4-tetrahydro­naphthalene and cyclopropane­methanol + isopropyl­cyclohexane, the excess molar volumes are positive over the entire range of molar fractions at all test temperatures, and the maximum values of V m E are both around x 1 = 0.6, as shown in Figure a and Figure c. The intermolecular force and molecular structure are the main factors that affect the excess molar volume. , As for the binary system containing alcohol, the intermolecular interactions play a more significant role for hydrogen bonding. ,, The hydrogen bond between the cyclopropyl­methanol molecules will be broken when the alkanes 1,2,3,4-tetrahydro­naphthalene or isopropyl­cyclohexane are added, so the positive excess molar volume of the binary mixtures can be observed. Obviously, the excess molar volume values of these two systems increase with the temperature increasing, which occurs because hydrogen bonds are more easily broken at high temperatures.…”
Section: Results and Discussionmentioning
confidence: 89%
“…20,21 As for the binary system containing alcohol, the intermolecular interactions play a more significant role for hydrogen bonding. 13,22,23 The hydrogen bond between the cyclopropylmethanol molecules will be broken when the alkanes 1,2,3,4-tetrahydronaphthalene or isopropylcyclohexane are added, so the positive excess molar volume of the binary mixtures can be observed. Obviously, the excess molar volume values of these two systems increase with the temperature increasing, which occurs because hydrogen bonds are more easily broken at high temperatures.…”
Section: Resultsmentioning
confidence: 99%